Immune damage mechanisms of COVID-19 and novel strategies in prevention and control of epidemic - Sun, Yuting; Luo, Bin; Liu, Yueping; Wu, Yuzhang; Chen, Yongwen (Frontiers in Immunology, 2023)
Caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), Coronavirus Disease 2019 (COVID-19) has diverse clinical manifestations which is the main feature of the disease, and the fundamental reason is the different immune response in different bodies among population. The damage mechanisms of critical illness by SARS-CoV-2 and its variants, such as hyperinflammatory response, double edged function of type-I interferon, and hyperactivation of the completement system, are the same as other critical illnesses. Targeted for specific immune damage mechanisms of COVID-19, we scored the first to put forward that the responses of T cells induced by acute virus infection result in “acute T cell exhaustion” in elderly patients, which is not only the peripheral exhaustion with quantity reduction and dysfunction of T cells, but also the central exhaustion that central immune organs lost immune homeostasis over peripheral immune organs, while the increased thymic output could alleviate the severity and reduce the mortality of the disease with the help of medication. We discovered that immune responses raised by SARS-CoV-2 could also attack secondary lymphoid organs, such as spleen and lymphoid nodes, and kidney besides the lung which we generally recognize. Integrated with the knowledge of mechanisms of immune protection, we developed coronavirus antigen diagnostic kit and therapeutic monoclonal antibody. In the future we will further investigate the mechanisms of immune damage and immune protection raised by coronavirus infection, in order to provide more scientific strategies for the development of new vaccines and immunotherapies.